Islet autoantibody status in a multi-ethnic UK clinic cohort of children presenting with diabetes. Issue 4 (19th November 2014) - Perchard, R; MacDonald, D; Say, J; Pitts, J; Pye, S; Allgrove, J; Banerjee, K; Amin, R
Abstract : Objective: We prospectively determined islet autoantibody status in children presenting with diabetes to a single UK region in relation to ethnicity. Design: 316 (68.0% non-white) children presenting with diabetes between 2006 and 2013 were tested centrally for islet cell autoantibodies (ICA) and glutamic acid decarboxylase autoantibodies (GAD-65) at diagnosis, and if negative for both, tested for insulin autoantibodies (IAA). The assay used to measure GAD-65 autoantibodies changed from an in-house to a standardised ELISA method during the study. Results: Even with use of the standardised ELISA method, 25.8% of children assigned a diagnosis of type 1 diabetes still tested negative for all three autoantibodies. 30% of children assigned a diagnosis of type 2 diabetes were autoantibody positive, and these had the highest glycated haemoglobin (HbA1c) levels at 12 months follow-up compared with other groups (p value for analysis of variance <0.001), although the sample size was small. Autoantibody positivity was similar between non-white and white children regardless of assay used (60.0% (n=129) vs 56.4% (n=57), χ 2 =0.9, p=0.35), as was mean GAD-65 autoantibody levels, but fewer non-white children had two or more autoantibodies detectable (13% (n=28) vs 27.7% (n=28), χ 2 =12.1, p=0.001). Conclusions: Islet autoantibody positivity was associated with a more severe phenotype, as demonstrated by poorer glycaemic control, regardless of assigned diabetes subtype. Positivity did not differ by ethnic group.